The effectiveness of a moral intelligence training program in reducing secondary school students’ academic entitlement - Abdellatif, Mohamed; Elagamy, Aida AbdElaal; Abdelgawad, Basyouny Ismail Abdelgawad (Research Journal in Advanced Humanities, 2024)
The research aimed to investigate the effectiveness of a training program based on moral intelligence components in reducing academic entitlement among secondary school students. The study sample consisted of a single experimental group of (32) students. The researcher administered the Academic Entitlement Scale (pre-test) to the participants before the moral intelligence-based training program, then after the program (post-test), and again a month later (as a follow-up assessment). Through statistical data processing using the t-test, the study results revealed significant differences in the mean scores of the experimental group on the Academic Entitlement Scale and its components between the pre-test and post-test in favor of the post-test. However, there were no statistically significant differences in the mean scores of the experimental group on the Academic Entitlement Scale and its components between the post-test and follow-up test (a month later). The researcher provided a comprehensive discussion of the study variables: academic entitlement and its components, and the moral intelligence-based training program in the current study. Additionally, recommendations and proposed future research were presented